ANALISIS PELAKSANAAN USAHA WARALABA MINUMAN CHESEE TEA DI KOTA PEKANBARU DI TINJAU DARI PERATURAN MENTERI PERDAGANGAN NOMOR 71 TAHUN 2019 TENTANG PENYELENGGARA WARALABA - Rokhimatul Isnaini; Maria Maya Lestari; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In Indonesia, the legal rules regarding Franchise are not yet complete. Wecan observe this indicator from the legal provisions governing franchise business,which so far have only been regulated in one (1) Government Regulation and one(1) Ministerial Regulation, as mentioned above. The regulation through law hasnot been touched by the government. Ignorance of business actors to the laws andregulations is the responsibility of the government on this issue.This type of research can be classified in the type of sociological lawresearch (empirical), because in this study the author directly conducts researchon the location or place studied. This research was conducted in the city ofPekanbaru. While the population and sample are the cheese tea franchisebusiness group and the Head of the Pekanbaru City Industry and Trade Office.Sources of data used are primary data, and secondary data. Data collectiontechniques in this study were interviews, and literature review.The conclusions that can be obtained from the results of the study are: First, thelegal awareness of franchise business actors in the implementation of a localcheese tea drink franchise business in the city of Pekanbaru in terms of theMinister of Trade Regulation Number 71 of 2019 concerning FranchiseOperators is still very low. This can be seen from the Regulation of the Minister ofTrade Number 71 of 2019 concerning the Implementation of Franchising as a newlegal basis in regulating franchise businesses in Indonesia in Article 2 paragraph(2) has determined that Franchising must meet several criteria. the criteria inArticle 2 paragraph (2) of the Regulation of the Minister of Trade Number 71 of2019 concerning Franchise Operators. Second, good faith in carrying out theobligations of the agreement by the franchisee but not being carried out inaccordance with the agreement and Regulation of the Minister of Trade Number71 of 2019 concerning Franchise Organizers, which has a detrimental effect onthe franchisee and consumers.Keywords: Implementation, Franchise, Cheese Tea Drink